Aneursymal Bone Cyst: An Uncommon Paraspinal Tumor in Children. Issue 2 (March 2019) - Shah, Nilay; Scharschmidt, Thomas; Fung, Bonita; Conces, Miriam; Setty, Bhuvana A.
Abstract : Paraspinal tumors with benign histology in the absence of trauma rarely arise in children. Treatment of such benign tumors, in contrast to malignancies, generally consists of surgical resection of the lesion with confirmation of histology via pathologic evaluation. We present a pediatric case of an atraumatic paraspinal mass with a histologic diagnosis of aneurysmal bone cyst, and USP6 gene rearrangement supporting the histologic diagnosis. The patient underwent gross total resection of the paraspinal lesion with no additional intervention. We highlight the differential diagnosis of paraspinal tumors in children and key features that led to the diagnosis in this patient.